Analysis of Numeracy Ability and Mathematical Anxiety of Junior High School Students - Maisaroh Tamrin; Al Jupri; Kusnandi Kusnandi (Southeast Asian Mathematics Education Journal, 2026)
Numeracy refers to an individual's ability to apply mathematical knowledge in everyday life to solve problems, analyse situations, and evaluate the results of their solutions. This study aims to assess the level of numeracy, mathematical anxiety, and the relationship between these two factors among grade IX junior high school students. The methodology employed is a case study with a qualitative approach. The subjects include 32 grade IX students from a junior high school in Bandung who have studied the topic of flat-sided solid figures. Data collection involved test techniques for numeracy assessments and non-test methods, including mathematical anxiety questionnaires and interview guidelines. The findings indicate that most students' numeracy abilities fall within the moderate range and that they experience moderate levels of mathematical anxiety. Students with low levels of mathematical anxiety demonstrated strong numeracy ability, as evidenced by meeting nearly all indicators of numeracy ability. Students exhibiting moderate mathematical anxiety displayed varying levels of numeracy, meeting 1 to 3 indicators of numeracy ability. In contrast, students with high levels of mathematical anxiety struggled with low numeracy ability, achieving only 1 or none of the numeracy indicators. These findings suggest the importance of integrating strategies that address both cognitive and emotional aspects of mathematics learning. Teachers are encouraged to design instructional approaches that reduce students’ mathematical anxiety while simultaneously strengthening their numeracy ability.